The Influence of a Tuition Fee Increase on the Drop-out Rate of the Nursing Program - Rumyana Stoyanova; Slaveyah Goranova (Journal of Economy Culture and Society)
The aim of the study is to further delve into the question of whether an increase in tuition fee could have a significant impact on the positive outcome of the sacrifice-for-gain assessment among Nursing students. We used an SPSS17.0 to analyze data from an anonymous survey of 160 Nursing students from March of 2016. The results show that the majority of students consider the current tuition fee to be “too high”. An increase in excess of 30% of the tuition fee would lead to a drop of 68.8% or more in the percentage of students willing to continue their education. In order to determine the impact of a tuition fee increase on the respondents’ decision to drop out, three models were tested: 1) the drop-out rate is linearly dependent only on the degree of the tuition fee increase; 2) the drop-out rate depends on multiple factors such as tuition fee increase, year of study, and intrinsic motivational factors; and 3) the drop-out rate depends on intrinsic motivational factors. The models without the variable tuition fee have more predictive power. The study found that only 4% of the drop-out decision is motivated by a potential increase in tuition fee.